Peningkatan Keterampilan Berbicara Bahasa Inggris Melalui Program English Conversation Club bagi Siswa SMP St. Antonius Nabire - Whisnubrata, Antonius Awan Asta Adhiprana; Dimara, Johanes; Jasmari, Jasmari; Rangkoly, Santji Afi; Hidayatillah, Tut (Lembaga Dongan Dosen, 2024)
English speaking skills are an important competency that students need to have, especially in facing the challenges of globalization. However, at SMP St. Antonius Nabire, the English speaking skills of grade VII students are still low due to the lack of opportunities to practice and exposure to the language. This community service program aims to improve students' English speaking skills through the English Conversation Club. The methods used are structured discussions, conversation simulations, and light debates in English, which are carried out in weekly sessions for several months. Active student participation in a supportive and pressure-free environment is the main focus of this activity. The results showed a significant increase in students' speaking skills, including fluency, pronunciation, and vocabulary. More than 70% of students experienced an increase in their English speaking skills and increased self-confidence. However, there were several weaknesses, such as limited implementation time and variations in student abilities that required further adjustments. The conclusion of this activity is that the English Conversation Club is effective in improving the English speaking skills of grade VII students at SMP St. Antonius Nabire. In the future, technology integration and expansion of the program to other schools can be the next steps to increase the positive impact of this program.